Generative AI in Digital Marketing Strategy: Transforming Brand Communication and Consumer Engagement - Putra, Halim Dwi; Juwita Azizah (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2026)
The rapid adoption of generative artificial intelligence (AI) in digital marketing has transformed how businesses communicate with consumers and build brand engagement. However, small and medium-sized enterprises (SMEs) in peripheral regions such as Bengkalis Island still face challenges in adopting advanced digital marketing tools due to limited technological literacy, marketing capabilities, and access to digital resources. This study explores the role of generative AI in enhancing digital marketing strategies to strengthen brand communication and consumer engagement among local businesses in Bengkalis Island. The importance of this topic lies in the growing need for SMEs in remote and island regions to remain competitive in the digital economy while adapting to emerging AI-driven marketing technologies. Using a mixed-method approach within a community service framework, the study involved digital marketing training, generative AI workshops, and mentoring sessions for local entrepreneurs. Data were collected through surveys, interviews, and observational evaluation of participants’ digital marketing practices before and after the program. The findings indicate that the integration of generative AI tools significantly improved participants’ ability to produce marketing content, enhance brand storytelling, and increase online consumer interaction. These results highlight the potential of generative AI as a practical and scalable solution for strengthening digital marketing capabilities in geographically peripheral communities